When the whole world is watching: A motivations-based account of selective expression and exposure. (October 2017) - Coppini, David; Duncan, Megan A.; McLeod, Douglas M.; Wise, David A.; Bialik, Kristen E.; Wu, Yin
Abstract: This study integrates theories of selective exposure with an updated uses and gratifications typology to account for partisans' motivations for consuming and sharing ideologically consistent information. By experimentally manipulating the visibility of an individual's media choices, we investigated differences in news selection choices when they are public and when they are private. Based on a sample of college students (N = 192), our results yield three important insights. First, motivations related to identity and opinion management are more likely to be activated when news choices are public. Second, further analysis shows that liberals were more likely to activate motivations related to identity and opinion management in the public condition. Third, our findings suggest that, among conservative respondents, the public condition elicited more politically motivated information selectivity, while for liberal respondents the private condition was more likely to lead to politically motivated choices. Highlights: Typology of motivations for consuming and sharing news is proposed. Identity and opinion management are more significant when news choices are public. Conservatives more likely to engage in selective expression. Liberals were more likely to engage in selective exposure.